ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT DALAM MENGELOLA KEUANGAN DENGAN NIAT SEBAGAI VARIABEL INTERVENING - Rangkuti, Anisa; Fuad, Muhammad; Dewi, Meutia (JURSIMA, 2023)
This study aims to analyze the influence of several factors that are seen as influencing people's behavior in managing finances, with intention as an intervening variable. Independent variables include financial literacy, financial attitudes, and sources of income. The research location was in Yusuf Hasyem Hamlet, Gampong Tengoh - Langsa City, with 100 households as respondents. The data analysis method used is multiple linear regression analysis, path analysis, t-test, F-test, coefficient of determination and Sobel test. The results of the multiple linear regression show that financial literacy, financial attitudes, and identified intentions have a positive effect on people's financial management behavior; while the source of income has a negative effect on financial management behavior. Based on the results of the t-test, it is proven that financial literacy has no significant effect on financial management behavior; but on financial attitudes, sources of income and intentions proved to have a significant effect on financial management behavior. The results of the F-test show that financial literacy, financial attitudes, sources of income and intentions simultaneously have a significant effect on financial management behavior. Based on the results of the Sobel test, it was found that intention was not able to mediate financial literacy and income sources on financial management behavior, but was able to mediate financial attitudes towards financial management behavior. The results of the coefficient of determination of financial literacy, financial attitudes, sources of income and intention to contribute 20.8% while the remaining 79.2% are influenced by other variables not examined by this study.